PEMBINAAN PERSONEL MESSING CATTERING GUNA MENINGKATKAN PROFESIONALISME DI BIDANG PELAYANAN PERSONEL LANUD HALIM PERDANAKUSUMA - Henry Christian Hutagaol; Yusuf Ali; Andi Arman (Universitas Perrtahanan Indonesia (UNHAN), 2023)
Halim Perdanakusuma Air Base plays a significant role in supporting personnel protocol service activities for securing VVIP/VIP individuals and serving VVIP/VIP guests. This research focuses on optimizing the training of Messing Cattering personnel at Halim Perdanakusuma Air Base to enhance professionalism and service quality when facing complex VIP/VVIP guests. A qualitative method, including interviews, observations, and document analysis, was utilized to gather data from Messing Cattering personnel. The results revealed several challenges in personnel training, such as handling the complexity of VIP/VVIP guests' requests, adhering to strict protocol requirements, facing limited resource availability, and dealing with high-pressure situations. Recommendations for improvement include adopting a holistic approach to personnel training, involving all levels of staff, strengthening the service system, and establishing a dedicated mess for VIP/VVIP guests. Additionally, implementing training and educational programs are vital to elevate professionalism and service quality. By taking these steps, it is expected that the quality of service provided when encountering challenges from VIP/VVIP guests will significantly improve